The Liberal Ethics of Non-Interference and the Pareto Principle - Marco Mariotti; Roberto Veneziani (University of Massachusetts, Department of Economics, 2014)
We analyse the liberal ethics of noninterference applied to social choice. A liberal principle capturing noninterfering views of society and inspired by John Stuart Mill's conception of liberty, is examined. The principle captures the idea that society should not penalise agents after changes in their situation that do not affect others. An impos- sibility for liberal approaches is highlighted: every social decision rule that satisfies unanimity and a general principle of noninterference must be dictatorial. This raises some important issues for liberal approaches in social choice and political philosophy.
Keywords: 330; Liberalism; Harm Principle; Non-Interference; Impossibility